1993
DOI: 10.1016/0006-3223(93)90100-r
|View full text |Cite
|
Sign up to set email alerts
|

Memory deficits associated with chronic fatigue immune dysfunction syndrome

Abstract: Performance on tests of memory in 39 patients who met Center for Disease Control (CDC) criteria for chronic fatigue immune dysfunction syndrome (CFIDS) was compared with 23 depressed patients (DSM-III-R) and 129 healthy controls. Although the CFIDS patients had normal neuropsychological profiles, they significantly overestimated their ability (metamemory), performed significantly worse on tests of recall as context increased (e.g., recognition), made more errors when rehearsal was prevented, and had delayed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 19 publications
4
41
0
Order By: Relevance
“…This finding therefore supports those of other authors who have also provided objective evidence for poor attention within the CFS population (McDonald et al 1993 ;Ray et al 1993 ;Sandman et al 1993 ;Cope et al 1995 ;Marshall et al 1997 ;Johnson et al 1998). The impairment the CFS group showed in attention was not accounted for by differences in mood.…”
Section: Discussionsupporting
confidence: 91%
“…This finding therefore supports those of other authors who have also provided objective evidence for poor attention within the CFS population (McDonald et al 1993 ;Ray et al 1993 ;Sandman et al 1993 ;Cope et al 1995 ;Marshall et al 1997 ;Johnson et al 1998). The impairment the CFS group showed in attention was not accounted for by differences in mood.…”
Section: Discussionsupporting
confidence: 91%
“…Specific deficits were noted only on tests of complex visual reproduction. Most unusually patients per-formed worse in cued situations, also noted elsewhere [65]. Grafman and colleagues concluded that neuropsychological deficits in CFS are relatively modest, and correlate with measures of affect [60].…”
Section: Psychiatry and Cfsmentioning
confidence: 59%
“…In contrast to Riccio et al (1992) and Sandman et al (1993), other investigators have concluded the cognitive abilities of CFS patients are not significantly impaired. Schmaling et al (1994), compared the performance of a group of CFS patients to published norms and to a control group comprised of physically healthy depressed patients.…”
Section: Studies Employing Control Groupsmentioning
confidence: 79%